2019
DOI: 10.1002/ajcp.12322
|View full text |Cite
|
Sign up to set email alerts
|

Elaborating the Connection between Social Class and Classism in College

Abstract: Highlights Financial stress is a key predictor of classism among college students. Financial stress predicts classism across immigration status and race. For U.S. born students, higher reported social class predicts greater exposure to classist narratives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…Some students of color face intersectional discrimination, such as that based in heterosexism, homophobia, transphobia, classism, xenophobia, ableism, and religious discrimination. Furthermore, many students of color experience certain forms of discrimination, such as classism, differently than White students who are coping with economic struggles do, as students of color do not benefit from race privilege (Cattaneo et al, 2019). Additionally, class differences are evident between many U.S. students of color and international students.…”
Section: Experiences Of Students Of Color On College Campusesmentioning
confidence: 99%
“…Some students of color face intersectional discrimination, such as that based in heterosexism, homophobia, transphobia, classism, xenophobia, ableism, and religious discrimination. Furthermore, many students of color experience certain forms of discrimination, such as classism, differently than White students who are coping with economic struggles do, as students of color do not benefit from race privilege (Cattaneo et al, 2019). Additionally, class differences are evident between many U.S. students of color and international students.…”
Section: Experiences Of Students Of Color On College Campusesmentioning
confidence: 99%
“…The measurement of social class is complex, and the literature is clear that strategies must be matched to research questions and population (Diemer et al, 2013). For college students, in prior work we have found that the current level of financial stress, rather than their parents' resources or status or their sense of deprivation while growing up, is the most salient aspect of social class (Cattaneo, Chan, et al, 2019;Rubin et al, 2014).…”
Section: Social Classmentioning
confidence: 99%
“…The College Financial Stress Scale. The College Financial Stress Scale was created by the authors for the purpose of this data collection, and its validation is described in Cattaneo, Chan, et al (2019). It includes two subscales: the Current Financial Stress subscale includes seven items such as "Currently, considering all of the financial resources I have available, I have more money coming in than I have going out" and "Whatever happens, I am confident I will be financially secure next year" (responses given on a 1-5 Likert scale).…”
Section: Social Classmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, while microaggressions may occur in person to person interactions, they are also communicated through institutional classism, that is, institutions operating in a way that privileges middle and upper‐SES students (see Locke and Trolian 2018 and Smith and Redington 2010 for brief reviews and discussions of class‐based microaggressions). Studies show that classism is pervasive on college campuses (Cattaneo et al 2019; Langhout, Rosselli, and Feinstein 2007; see also Jack 2018; Lee 2016). LIFGWC students report heightened awareness of class differences compared to their middle‐ and upper‐class peers (Warnock et al 2018) and experience classism to detrimental effect (Ellis et al 2019; Langhout et al 2007).…”
Section: Background and Literaturementioning
confidence: 99%